Students’ Writing Procedure Text Mastery - Rayendriani Fahmei Lubis; Nur Khoiria Hasibuan (Institut Agama Islam Negeri (IAIN) Padangsidimpuan, 2020)
This research focused on the students’ ability in writing procedure text at grade XI MAS NU Sibuhuan. Based on first observation, the students are difficult to create text because they have lack of vocabulary and confidence in expressing idea into written form. The researcher applied mixed method by giving essay test and interview to evaluate the students’ writing in procedure text and identifying students’ difficulties. Students’ of XI MIA 2 that consisted of 33 were as sample. The indicators of test divided into content, organization, syntax, vocabulary and mechanics. The result of this research has found that students’ ability in writing procedure text lied on mean 57.56 score. It means that students’ writing procedure text ability categorize into poor category. Moreover, the students’ difficulties are vocabulary mastery and syntax.